Internalisasi Nilai-nilai Multikultural dalam Pembelajaran Pendidikan Agama Islam di Sekolah (Pendidikan Tanpa Kekerasan) - Sapendi Sapendi (Raheema, 2015)
Multicultural education is a false sosial device to boost the schools’ participation in order to build the awareness of multicultural society. It will be useful to strengthen the tolerance to realize the ability of working together above the differences. Teachers are the important roles on spreading the multicultural values to create the harmonious community. Furthermore, teachers are expected to introduce the symbols of nationality insight through the education process in the class or in the vast society. Besides, teachers are supposed to actively participate on the development of multiculturalism in Indonesia. So that, the exclusivity which triggers the interpersona or group conflict could be decreased. Teachers, particularly the religion teacher should teach not only the values in the religion’s rituals, but also the universal values, such as justice, equality, humanity, kindness, honesty, and so on. Therefore, the religion teacher should thoughtfully profound the universal concepts believed by their own religion.